The nature, extent and effect of skills shortages on skills migration in South Africa - Fatima Rasool; Christoff J. Botha (SA Journal of Human Resource Management, 2011)
Orientation: South Africa is currently experiencing a serious shortage of skilled workers. It has a negative effect on South Africa’s economic prospects and on global participation in South Africa (SA). This skills shortage severely affects socioeconomic growth and development in SA. Research purpose: This study focuses on the causes and effects of the skills shortages in South Africa.